Experimental Study on Fracturing Fluid Damage of Tight Sandstone Reservoirs Based on Nuclear Magnetic Resonance Technology - Deng, Yongquan (International Journal of Natural Resources and Environmental Studies, 2025)
This study based on nuclear magnetic resonance (NMR) technology, systematically evaluated the microscopic damage mechanism of fracturing fluids on tight sandstone reservoirs. Through core displacement experiments, combined with permeability tests and T2 spectrum analysis, the impact of fracturing fluids on the pore structure and seepage capacity of the reservoir was quantified. The experimental results showed that the core permeability significantly decreased (35.76% to 66.41%) after fracturing fluid displacement, with an average matrix damage rate of 54.55%. The NMR T2 spectrum indicated that the high-molecular components in the fracturing fluid preferentially invaded and adhered to the medium and large pores, causing their pore size distribution to shift towards micro and small pores, and the overall pore volume decreased. X-ray diffraction analysis revealed that the water-induced swelling of clay minerals further exacerbated the blockage of medium to large pore throats, destroying the seepage channels. The study confirmed that the main cause of damage to tight sandstone reservoirs was the physical blockage of medium to large pore throats by fracturing fluids and the water sensitivity effect of clay minerals, providing key experimental evidence for the optimization of fracturing fluid formulations and reservoir protection.